Efektifitas Pelayanan Kesehatan Sebagai Arena Politik: Studi Implementasi BPJS di RSUD Kota Dumai - Fitra Hadi Khaz (AAI Pengda Riau, 2026)
This study aims to analyze how health services—particularly the implementation of the BPJS Health program—function as part of the local political dynamics at RSUD Kota Dumai. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation studies. The main theoretical frameworks used are Grindle's policy implementation theory and Frederickson's perspective on the politics of public service. The findings indicate that BPJS health services are not only influenced by administrative structures but also by the local political context, including public pressure, regional government image, and bureaucratic actors' strategies. Furthermore, service quality is assessed through the dimensions of tangibility, responsiveness, assurance, reliability, and empathy. In conclusion, healthcare delivery at RSUD Kota Dumai reflects a micro-political arena in which public policy is contested and reinterpreted by local actors.